Powering Batteryless Embedded Platforms by Piezoelectric Transducers: A Pilot Study - Prauzek, Michal; Konecny, Jaromir; Vitasek, Martin; Bajgar, Vaclav; Musilek, Petr (Elektronika ir Elektrotechnika, 2019)
This contribution presents a pilot study on powering battery-less embedded systems. First, a piezoelectric transducer principle and low-power techniques are reviewed in the background section. In the experimental part, the authors describe a testing setup consisting of piezoelectric transducer, DC/DC converter with energy storage, and evaluation microcontroller platform (FRDM KL25Z). Three types of experiments have been conducted for two voltage configurations including charging speed, continuous operation and discharge test. Results presented in this article concentrate on power supply voltage (1.8 V and 3.3 V), total efficiency (67.16 % and 76.75 %) and operation times (24.28 s and 15 s) of the embedded system. DOI: 10.5755/j01.eie.25.2.23201